Correlations between macrophage/microglial activation marker sTREM-2 and measures of T-cell activation, neuroaxonal damage and disease severity in multiple sclerosis. Issue 2 (May 2021) - Ioannides, Zara A; Csurhes, Peter A; Swayne, Andrew; Foubert, Philippe; Aftab, Blake T; Pender, Michael P
Background: Soluble triggering receptor expressed on myeloid cells-2 (sTREM-2) is a marker of macrophage and microglial activation and is increased in the cerebrospinal fluid (CSF) in multiple sclerosis (MS). Objective: To determine the relationships among sTREM-2, T cell activation, neuroaxonal damage and clinical features of MS. Methods: Enzyme-linked immunosorbent assays were used to measure the levels of sTREM-2, soluble CD27 (sCD27, a marker of T cell activation), neurofilament light chain (NfL) and phosphorylated neurofilament heavy chain (pNfH) in the CSF of 42 patients with MS (including nine with clinically isolated syndrome) and 15 patients with other neurological diseases (OND) and in the serum of 164 patients with MS, 87 patients with OND and 62 healthy controls. Results: sTREM-2 was significantly elevated in the CSF ( p  = 0.012), but not in the serum, in MS compared to OND. In MS, CSF sTREM-2 correlated positively with CSF sCD27 ( p  = 0.005), CSF NfL ( p  = 0.0001), CSF pNfH ( p  = 0.0006), Expanded Disability Status Scale (EDSS) score ( p  = 0.0079) and MS Severity Score (MSSS) ( p  = 0.0006). Conclusion: In MS the level of sTREM-2 in the CSF is related to measures of T cell activation (sCD27), neuroaxonal damage (NfL and pNfH), disability (EDSS) and disease severity (MSSS).